2020
DOI: 10.1002/ird.2528
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring water status in apple trees using a sensitive morning crop water stress index*

Abstract: The crop water stress index (CWSI) has shown to be a good indicator of water status in fruit trees. Conventional CWSI measured over solar noon is widely used to monitor plant water status. This study compared the theoretical CWSI averaged over morning hours, CWSImo, and over solar noon hours, CWSImd, of apple trees. This study also assessed their sensitivity to the changes in soil water status (soil water deficit [SWD, %] and soil water potential [SWP, kPa]) at different root zone depths. Four different types … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 59 publications
(79 reference statements)
1
1
0
Order By: Relevance
“…The values of CWSI calculated in this study were similar to those reported by Egea et al. (2017) in olive trees under severe water stress but lower than those reported in apple trees under no water stress by Mohamed et al. (2021) .…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The values of CWSI calculated in this study were similar to those reported by Egea et al. (2017) in olive trees under severe water stress but lower than those reported in apple trees under no water stress by Mohamed et al. (2021) .…”
Section: Discussionsupporting
confidence: 80%
“…(2021) . The difference in the values reported by Mohamed et al. (2021) under similar environmental conditions might be attributed to the calculation of the NWSB, as that study used an approach based on environmental conditions which might overestimate their calculation of the CWSI compared to when non-stressed leaves are directly measured.…”
Section: Discussionmentioning
confidence: 87%
“…In practice, CWSI from remote sensing has proved useful for estimating PWS in terms of both water potential (Ψ stem and Ψ leaf ) and gas exchange (g s ) in woody fruit crops. Strong correlations have been shown in multiple crops, such as grapevine [105,238,247], olive [231,[248][249][250], almond [251], plum [243], peach [237,245,252], apple [253], cherry [223], pear [227], and citrus [228,254,255], among others. In 2023, Mortazavi et al developed a predictive model for determining the Ψ stem in almond and pistachio using vegetation indices obtained from aerial images through a machine learning approach [256].…”
Section: Thermal Sensingmentioning
confidence: 99%